The Evolving Approach to Treating Syndesmotic Injuries in the Elite Athlete: An International Perspective. Issue 4 (16th October 2019) - Hunt, Kenneth; Challa, Shanthan; D'Hooghe, Pieter; Kumparatana, Pam; Phisitkul, Phinit; McCormick, Jeremy; Amendola, Annunziato
Category: Ankle, Sports Introduction/Purpose: There exists little consensus regarding optimal treatment protocols for syndesmotic injuries. Orthopaedic clinicians have implemented a variety of treatment strategies, ranging from immobilization to screw fixation to new flexible fixation devices. While the body of literature is growing with regard to both the biomechanics and clinical outcomes for various constructs and rehabilitation protocols, there is little consensus on the optimal treatment and return to sport strategy for these injuries. We endeavored to assess current approaches to syndesmotic injures by orthopedic foot and ankle specialists around the world in 6 athlete scenarios with increasing degree of injury. Commensurate with the lack of available data to guide treatments, we hypothesize that there will be variability in the treatment and management strategies for syndesmotic injuries. Methods: A REDcap survey was created with 27 questions, including respondent demographics, indications for treatment of syndesmotic injuries, preferred treatment, preferred technique for repairing the syndesmosis and post-operative management. Respondents were asked to choose their preferred fixation device and post-operative return to play protocols in six different athlete scenarios (moderate impact, high impact and very high impact and each with/without complete deltoid injury). The survey was disseminated among the memberships of 18 North American and International medical societies. Society members were surveyed via three emails disseminated 2 weeks apart. Frequencies and percentages were calculated for all categorical responses. Results: A total of 596 providers responded to the survey, including 337 American surgeons and 259 members of various international societies. There was a 70% survey completion rate with a wide geographic distribution among respondents. Flexible devices were the preferred fixation construct (48.1%), followed by screws (27.5%), hybrid fixation (18.5%) and other (5.9%). There was a higher preference for flexible devices among sports medicine trained providers. 62% of respondents noted that their rehabilitation protocols would not change for each athlete scenario. Considerable variability was present in anticipated full return to sport, ranging from immediately following injury to 6 months post-op (Fig 1). One-third of respondents indicated that they repair the deltoid greater than 50% of the time when injured. Conclusion: We found a wide variety of indications and treatment constructs employed by orthopaedic surgeons for athletes with ligamentous syndesmotic injuries requiring fixation. Although, flexible fixation devices are the preferred among all respondents but there was a considerable variability in device choices. Fellowship training also appears to affect the preferred fixation device choice. There also exists substantial variability in expected return to play for every athlete scenario (Fig 1). The diversity in approaches and post-operative recommendations underscores the need for evidence-based guidelines to inform management of syndesmotic injuries.